Marketing Performance Measurement Ability and Firm Performance - Kuncoro, Amin (Journal of Economics and Public Health, 2024)
The ability to measure marketing performance has become a pivotal factor influencing a firm’s overall success. This study explores the relationship between marketing performance measurement (MPM) capabilities and firm performance, with a focus on the mechanisms through which MPM drives better decision-making, resource allocation, and competitive advantage. By examining existing literature and case studies, we aim to provide actionable insights for businesses seeking to optimize their marketing strategies through enhanced measurement capabilities.